2013
DOI: 10.1007/s00339-013-7565-y
|View full text |Cite
|
Sign up to set email alerts
|

Hard X-ray photoelectron spectroscopy on buried, off-stoichiometric Co x Mn y Ge z (x:z=2:0.38) Heusler thin films

Abstract: Hard X-ray photoelectron spectroscopy on buried, off-stoichiometric Co x Mn y Ge z (x : z = 2 : 0.38) Heusler thin films.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…Another way to avoid spurious photoemission results due to degraded sample surfaces is the use of less surface-sensitive hard x-ray photoemission spectroscopy (HAXPES). The identification of several experimentally obtained intensity features with the density of states (DOS) was possible for materials like NiTi 0.9 Sc 0.1 Sn, NiMnSb or Co x Mn y Ge z (x : z = 2 : 0.38) thin Heusler films 50,51 . However, due to the low intensities of HAXPES experiments no spin resolved results are available up to now.…”
Section: B Experimental Detailsmentioning
confidence: 99%
“…Another way to avoid spurious photoemission results due to degraded sample surfaces is the use of less surface-sensitive hard x-ray photoemission spectroscopy (HAXPES). The identification of several experimentally obtained intensity features with the density of states (DOS) was possible for materials like NiTi 0.9 Sc 0.1 Sn, NiMnSb or Co x Mn y Ge z (x : z = 2 : 0.38) thin Heusler films 50,51 . However, due to the low intensities of HAXPES experiments no spin resolved results are available up to now.…”
Section: B Experimental Detailsmentioning
confidence: 99%
“…The CMFS thin film was deposited at RT using radiofrequency magnetron cosputtering from three targets, i.e., nearly stoichiometric CMS, Mn, and Fe, in an ultrahigh vacuum chamber (that has a base pressure of 6 × 10 [47], electronic, and magnetic properties [33][34][35][36][37][38][48][49][50]. The MgO buffer and barrier were deposited by electron beam evaporation in the same chamber at 400°C and RT, respectively.…”
Section: A Experimental Methodsmentioning
confidence: 99%
“…Picozzi et al predicted from first principles that half-metallicity in CMS and Co 2 MnGe (CMG) is lost for Co Mn antisites, where a Mn site is replaced by a Co atom, because of the appearance of minority-spin in gap states near E F , while half-metallicity is retained for Mn Co antisites, where a Co site is replaced by a Mn atom [33]. The effect of off-stoichiometry on the half-metallicity of CMS and CMG has been systematically investigated recently using various experimental approaches, including the tunneling magnetoresistance (TMR) ratios of MTJs [9][10][11][12], the saturation magnetization per formula unit of thin films [12], the surface spin polarization [42], the magnetic states as investigated by x-ray absorption spectroscopy and x-ray magnetic circular dichroism [43][44][45], and the electronic states as investigated through spin-resolved low-energy and hard x-ray photoelectron spectroscopy [46][47][48]. These experimental studies, along with first-principles calculations, demonstrated that Co Mn antisites induced by a Mn-deficient composition (the Mn composition α < 2 − β in the composition expression of Co 2 Mn α Si β ) is detrimental to the half-metallicity of CMS.…”
Section: Introductionmentioning
confidence: 99%